Body–Brain Connections: The Effects of Obesity and Behavioral Interventions on Neurocognitive Aging - Stillman, Chelsea M.; Weinstein, Andrea M.; Marsland, Anna L.; Gianaros, Peter J.; Erickson, Kirk I. (Frontiers in Aging Neuroscience, 2017)
Obesity is a growing public health problem in the United States, particularly in middle-aged and older adults. Although the key factors leading to a population increase in body weight are still under investigation, there is evidence that certain behavioral interventions can mitigate the negative cognitive and brain health (neurocognitive) consequences of obesity. The two primary behaviors most often targeted for weight loss are caloric intake and physical activity. These behaviors might have independent, as well as overlapping/synergistic effects on neurocognitive health. To date obesity is often described independently from behavioral interventions in regards to neurocognitive outcomes, yet there is conceptual and mechanistic overlap between these constructs. This review summarizes evidence linking obesity and modifiable behaviors, such as physical activity and diet, with brain morphology (e.g., gray and white matter volume and integrity), function (e.g., functional activation and connectivity), and cognitive functioning across the adult lifespan. In particular, we review evidence bearing on the following question: Are associations between obesity and brain health in aging adults modifiable by behavioral interventions?